A Multi-Centric Evaluation of AI-Driven Synthetic CT Generation Form Low Field Magnetic Resonance Imaging - Gungor, G.; Azria, D.; Balermpas, P.; Boldrini, L.; Chuong, M. D.; De Ridder, M.; Gevaert, T.; Hardy, L.; Kandiban, S.; Maingon, P.; Mittauer, K. E.; Ozyar, E.; et al. (ELSEVIER SCIENCE INC, 2022)
Annual Meeting of the American-Society-for-Radiation-Oncology (ASTRO), ELECTR NETWORK, OCT 23-26, 2022